Positivity and difference of influence of built environment around urban park on building energy consumption. (February 2023) - Wang, Peng; Yang, Yuting; Ji, Cheng; Huang, Lei
Highlights: Effects of built environment around park and building energy consumption (BEC) were explored. Compact high-rise buildings tend to reduce BEC when increasing road intersections. Sparse high-rise buildings around the urban parks can reduce BEC. Abstract: Built environment can improve thermal comfort and reduce building energy consumption. Among these, urban parks are considered as a major strategy for reducing building energy consumption. Understanding the relationship of built environment around the urban park on building energy consumption is thus critical. This study established grid groups with different built environment layouts around urban park from the perspective of 3D building characteristics, land cover and road network. Then the correlation relationship between built environment and building energy consumption was examined by using the spatial regressive model, and the positivity and difference of building environment effect on building energy consumption were analyzed and compared emphatically. The results showed that water body and road intersection can weaken the positive effect of impervious surface area (ISA) in compact high-rise building area, and water body can promote the negative effect of form factor (S/V) in sparse high-rise building area. Additionally, we found that the sparse high-rise buildings were conducive to the spread of cold air in the park compared to compact high-rise, which promoted the negative effects of S/V. Therefore, the built environment should be incorporated into urban planning to reduce building energy consumption.